Cation-conduction dominated hydrogels for durable zinc–iodine batteries - Yang, Jin-Lin (2024)
Zinc-iodine batteries have the potential to offer high energy-density aqueous energy storage, but their lifetime is limited by the rampant dendrite growth and the concurrent parasite side reactions on the Zn anode, as well as the shuttling of polyiodides. Herein, a cation-conduction dominated hydrogel electrolyte is designed to holistically enhance the stability of both zinc anode and iodine cathode. In this hydrogel electrolyte, anions are covalently anchored on hydrogel chains, and the major mobile ions in the electrolyte are restricted to be Zn2+ . Specifically, such a cation-conductive electrolyte results in a high zinc ion transference number (0.81) within the hydrogel and guides epitaxial Zn nucleation. Furthermore, the optimized Zn2+ solvation structure and the reconstructed hydrogen bond networks on hydrogel chains contribute to the reduced desolvation barrier and suppressed corrosion side reactions. On the iodine cathode side, the electrostatic repulsion between negative sulfonate groups and polyiodides hinders the loss of the iodine active material. This all-round electrolyte design renders zinc-iodine batteries with high reversibility, low self-discharge, and long lifespan.